دراسة تحليلية لواقع الصادرات الجزائرية تجاه السوق الموريتاني للفترة 2000-2022: Analyzing the realities of Algeria’s exports to Mauritanian market from 2000-2022 - µحيداس عبد القادر; مهر حاج أمحمد; مجدوبي شهرزاد (Journal of North African Economies, 2025)
The study aims to identify the importance of Algerian exports to the Mauritanian market by examining the reality of Algerian exports during the period from 2000 to 2022. It provides a general overview of the state of Mauritania and analyzes the major Algerian exports to the Mauritanian market. The study found that Algerian exports to Mauritania have shown a marginal increase overall during the study period, with an average of 35 million dollars, mostly consisting of oil exports. Non-oil exports primarily consisted of food products. The study also concluded that bilateral trade between the two countries is continuously evolving, reflected by increased export operations in recent years, especially after the opening of the land border crossing in 2018. Additionally, the study confirmed that the Mauritanian market is an attractive market for Algerian products. Based on the findings, the study recommended several measures, including the need to expedite the completion of the connecting road between the two countries, specifically the Tindouf-Zouerate road.